2019
DOI: 10.3390/ani9110974
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Soybean Meal with Urea in Diets for Heavy Fattening Lambs: Effects on Growth, Metabolic Profile and Meat Quality

Abstract: Simple SummaryThere is a renewed interest on the potential inclusion of urea in ruminant diets, reducing the contribution of vegetable protein supplements. This study was designed to evaluate the effect of replacing soybean meal with different proportions of urea in protein-rich diets for heavy fattening lambs (from 29 to 50 kg of live body weight). Our results suggest that 39% of soybean meal of such diets can be replaced with urea reducing the feeding costs without any adverse effects on feed efficiency, rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
4
13
1
Order By: Relevance
“…Ruminal NH 3 -N is an equilibrium between dietary N degradation, microbial protein synthesis utilization, and N absorption. Greater NH 3 -N production from dietary sources is not necessarily reflected in a higher ruminal NH 3 -N concentration [14]. The current meta-analysis shows urea supplementation had a minor effect on the microbial N supply and total protozoa population.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Ruminal NH 3 -N is an equilibrium between dietary N degradation, microbial protein synthesis utilization, and N absorption. Greater NH 3 -N production from dietary sources is not necessarily reflected in a higher ruminal NH 3 -N concentration [14]. The current meta-analysis shows urea supplementation had a minor effect on the microbial N supply and total protozoa population.…”
Section: Discussionmentioning
confidence: 59%
“…Ammonia accumulation from urea degradation may increase ruminal pH [13]. The rate of ureagenesis determines the disposal of bicarbonate and affects the maintenance of pH homeostasis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 3 g of ileal content was mixed with 6 ml of purified Milli-Q water and then acidified using 0.25 ml of sulfuric acid solution. NH 3 -N concentration in the rumen content was determined by a modified colorimetric method ( Wheatherburn, 1967 ) and SCFAs in ruminal and ileal contents were determined according to Saro et al (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the AMS inclusion level in the diets, no differences were observed in terms of the three meat colour coordinates. According to Saro et al (2019), diet is one of the extraneous factors affecting carcass characteristics and meat quality parameters. El bukhary (2005) also indicated that meat colour is affected by diet.…”
Section: Discussionmentioning
confidence: 99%